The teaching of statistical graphs: review of an interactive textbook for third grade in Costa Rican education: La enseñanza de los gráficos estadísticos: reseña de un libro de texto interactivo para tercer año de la educación costarricense - Monge Madriz, Carlos (2024)
This paper introduces an interactive statistics book designed for third-grade primary students, targeting both boys and girls aged approximately 8 to 9 years old. Developed in 2023, the material is centered around Costa Rican education, examining the significance of its activities pertaining to statistical graphics. The methodology involved skill identification, a review of a study on graphics in Costa Rican textbooks, consideration of theoretical aspects, activity design, content analysis, and validation by experts. The book promotes problem-solving, statistical argumentation, and the utilization of technology, aligning with the current mathematics curriculum in Costa Rican education. It stands as an innovative and comprehensive educational resource poised to enhance the teaching of statistics in primary education.